2(3ab+4bc-2x)x-3x(2ab-5cb-4x+2)=

Simple and best practice solution for 2(3ab+4bc-2x)x-3x(2ab-5cb-4x+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3ab+4bc-2x)x-3x(2ab-5cb-4x+2)= equation:


Simplifying
2(3ab + 4bc + -2x) * x + -3x(2ab + -5cb + -4x + 2) = 0

Reorder the terms for easier multiplication:
2x(3ab + 4bc + -2x) + -3x(2ab + -5cb + -4x + 2) = 0
(3ab * 2x + 4bc * 2x + -2x * 2x) + -3x(2ab + -5cb + -4x + 2) = 0
(6abx + 8bcx + -4x2) + -3x(2ab + -5cb + -4x + 2) = 0

Reorder the terms:
6abx + 8bcx + -4x2 + -3x(2 + 2ab + -5bc + -4x) = 0
6abx + 8bcx + -4x2 + (2 * -3x + 2ab * -3x + -5bc * -3x + -4x * -3x) = 0

Reorder the terms:
6abx + 8bcx + -4x2 + (-6abx + 15bcx + -6x + 12x2) = 0
6abx + 8bcx + -4x2 + (-6abx + 15bcx + -6x + 12x2) = 0

Reorder the terms:
6abx + -6abx + 8bcx + 15bcx + -6x + -4x2 + 12x2 = 0

Combine like terms: 6abx + -6abx = 0
0 + 8bcx + 15bcx + -6x + -4x2 + 12x2 = 0
8bcx + 15bcx + -6x + -4x2 + 12x2 = 0

Combine like terms: 8bcx + 15bcx = 23bcx
23bcx + -6x + -4x2 + 12x2 = 0

Combine like terms: -4x2 + 12x2 = 8x2
23bcx + -6x + 8x2 = 0

Solving
23bcx + -6x + 8x2 = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '6x' to each side of the equation.
23bcx + -6x + 6x + 8x2 = 0 + 6x

Combine like terms: -6x + 6x = 0
23bcx + 0 + 8x2 = 0 + 6x
23bcx + 8x2 = 0 + 6x
Remove the zero:
23bcx + 8x2 = 6x

Add '-8x2' to each side of the equation.
23bcx + 8x2 + -8x2 = 6x + -8x2

Combine like terms: 8x2 + -8x2 = 0
23bcx + 0 = 6x + -8x2
23bcx = 6x + -8x2

Divide each side by '23cx'.
b = 0.2608695652c-1 + -0.347826087c-1x

Simplifying
b = 0.2608695652c-1 + -0.347826087c-1x

See similar equations:

| -2-4=3x+5x | | 3x+4x+5x=12x | | x-7=2(x-7)-(x-7) | | 6(2+x)=5(1-4x) | | 5(4x+3)=18 | | 8w=.25 | | 8b^4(6b^5+10b)= | | y^2-37-4= | | 8w= | | 11(z+1)-3(z-1)=3(z-4)+4(z-1) | | 9x+8=5-(7x-8) | | -2v=.75 | | 0.3u-0.1=2.2u-5.8 | | 4(x+3)-1=27 | | x^2+5x=6whatisx | | -200=2(10x+10) | | 5x^2+x-14=-10 | | 9y^2-y+6=0 | | v^2-6v-7= | | X^3-2x^2-16x+32= | | 4x+8y=4slope | | 6x+7=(x+8) | | (x-3)(x+8)=0whatisx | | 6a-4whena=5 | | 1.7m^2=6.5n-4n+2.5m^2-n | | 8(7x-7)=45 | | 5-7(4x+6)=2 | | -6=-6v+4(v-6) | | (5w-8)(2w+9)=0 | | Ys+yz=tfory | | z+1.4z-1.6=1.5(z+1.4) | | 0=4v-6 |

Equations solver categories